Social practices and inequality measurement in pre-hispanic polities: diachronic notes from southern andes - López Lillo, Jordi A. (2023)
This communication seeks to explore political organization and dynamics from a comparative perspective over time, relying on three case studies which cover the so-called Formative (500 BC-AD 600), Regional Development (AD 1200-1450) and Late or Inca Periods (AD 1450-1550) in Northwest Argentina and South Bolivia. In each case, samples of several hundreds of residential units were used to calculate Gini coefficients; disaggregating them, additionally, by the different types of roofed and open surfaces within households. These analyses were then densified and put in perspective taking into account further archaeological records, as their crop fields, burials and other material indicators sensible to social inequality, in order to get a better understanding of each political configuration. As a result, it seems not only that, unlike those in Central Andes, the social processes that took place in this southern part led to the formation of agropastoral societies with low levels of centralization and wealth inequality during the Second Millennium BC, but also that the egalitarian polities of the First Millennium were far more complex and perhaps even internally competitive than assumed.